2013
DOI: 10.5262/tndt.2013.1003.04
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Acute Renal Failure in Central Anatolia

Abstract: OBJECTIVE: Our main purpose was to evaluate the epidemiological properties and mortality rate of this study and to evaluate the etiology and factors associated with mortality in patients with ARF. MATERIAL and METHODS:In this prospective observational study a total of 541 patients with ARF were assessed between January 2008 -January 2012. The etiological spectrum and predictors of mortality were evaluated in this population. RESULTS:The mean age was 64.9 ± 15.6 years and the majority of patients were male. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Medve et al (25), published that mortality was 49% in intensive care ARF patients, and risk factors wereage, sepsis, and mechanical ventilation. In a study conducted from Turkey, the mortality rate was found to be 7.4%, and among the causes of death, cardiopulmonary failure was 70%, and sepsis and myocardial infarction were 10% (28). In this study 79.3% of patients with ARF and 18% of patients without acute failure had deceased.…”
Section: Discussionmentioning
confidence: 48%
“…Medve et al (25), published that mortality was 49% in intensive care ARF patients, and risk factors wereage, sepsis, and mechanical ventilation. In a study conducted from Turkey, the mortality rate was found to be 7.4%, and among the causes of death, cardiopulmonary failure was 70%, and sepsis and myocardial infarction were 10% (28). In this study 79.3% of patients with ARF and 18% of patients without acute failure had deceased.…”
Section: Discussionmentioning
confidence: 48%